Effect of colpexin sphere on pelvic floor muscle strength in women with pelvic organ prolapse: A randomized controlled trial (a preliminary report) - Thitima Harnsomboon (2018)
Objective: The aim of this study was to assess the effect of Colpexin Sphere with pelvic floor exercise in women with stage I and II pelvic organ prolapse on improving pelvic floor muscle strength compared with the pelvic floor exercise only. Methods: The women were divided into two groups: one group used Colpexin Sphere with pelvic floor muscle exercise, and the other group did pelvic floor exercise only for a 16-week period. The efficacy was evaluated at baseline and 16-week for comparison of pelvic floor muscle strength. Results: A total of 50 women were enrolled and 48 women completed the full 16-week assessment. A statistically significant improvement in pelvic floor muscle strength as compared with baseline values and at 16 weeks was shown in both groups, with mean difference pull test contraction values of 2.25 + 3.28 N (P < 0.05) in the study group and 1.38 + 2.17 N (P < 0.05) in the control group. There was no statistically significant difference in improving pelvic floor muscle strength between the study and the control groups. Conclusion: Even though Colpexin Sphere plus pelvic floor exercise improved pelvic floor muscle strength, the improvement was not statistically different from exercise alone. © 2010 Springer-Verlag.